Penerapan model pembelajaran missouri mathematics project untuk meningkatkan kemampuan transfer of knowledge hots statistika pada peserta didik kelas iv sekolah dasar - Intan Permata Mahalia; Siti Istiyati; Anesa Surya (Didaktika Dwija Indria, 2019)
The purpose of this study is to improve HOTS Transfer of Knowledge capabilities on statistical question by applying the Missouri Matematics Project (MMP) learning model. This research is a Classrom Action Research and consist of two cycles. The subject of this study were fourth grade students of SD Negeri Pajang II Surakarta in the 2018/2019 academic year, totaling 26 students. The data collection technique of this study uses interviews, observation, test, and documentation. The data validity test technique of this research is the content validity. The analysis of the data used in this study is Miles-Huberman’s interactive analysis model. The initial condition of HOTS Transfer of Knowledge ability of fourth grade students resulted in completeness of C4 aspects by 7 students, C5 by 2 students, and C6 by 2 students. Cycle 1 meeting 1 completeness aspects of C4 were 13 stuents, C5 were 13 students, and C6 were 12 students. Cycle 1 meeting 2 completness aspects of C4 were 20 students, C5 were 15 students, and C6 were 15 students. Cycle 2 meeting 1 completness aspects of C4 were 21 students, C5 were 20 students, and C6 were 21 students. Cycle 2 meeting 2 completness aspects of C4 were 23 students, C5 were 23 students, and C6 were 22 students.